Correlation Between Different Selected Stress Biomarker and Slow Music Intervention Among First Year Medical Students (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Stress is the most common human experience. Excessive stress cause psychosocial health problems. It reduces self-confidence, academic performances and healthy development of an individual. The education in medical college is stressful due to vastness of academic syllabus. Beside this language problem, frequency of examination and high parental expectation may cause stress. Music plays an important role to improve person’s quality of life. It alters the mood and behavior. It can affect central and autonomic nervous system. The objective of the study to find out the  correlation between Perceived Stress Scale (PSS) score  change with systolic and diastolic blood pressure, serum cortisol and fasting blood sugar change after slow music intervention among first year medical college students.  Materials and methods: This experimental study was conducted in the Department of Physiology, Chittagong Medical College, Chattogram. Total 60 subjects of first year MBBS, with equal number of male and female, studying in Chittagong Medical College, Chattogram, were included by stratified random sampling method according to inclusion and exclusion criteria. Selected stress biomarkers - systolic and diastolic blood pressure, Perceived Stress Scale (PSS) score, serum cortisol and fasting blood sugar were recorded before and after 15 minutes of music intervention for 15 days.  Results: Result was compiled and compared after data collection by using SPSS-25. Pearson correlation coefficient was done to assess the relationship between changes in PSS score with changes of other stress biomarkers-systolic and diastolic blood pressure, serumcortisol and fasting blood sugar. p